1992
DOI: 10.1103/physrevc.45.2603
|View full text |Cite
|
Sign up to set email alerts
|

Extracting a value of the deuteron radius by reanalysis of the experimental data

Abstract: A new value, rD=1.9546+0.0021 fm, for the rms radius of the deuteron has been extracted by reanalyzing the experimental data for the ratio R (q ) of the deuteron to proton electric form factors and for the slope of the neutron electric form factor GE"(q') at q'=0. The short-range structures in the radia1 deuteron wave functions found for a certain class of potentials (e.g. , Kermode et al. and potential models presented here) cause an increase in the model values of the deuteron charge form factor CE{q ), but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
4
6
0
Order By: Relevance
“…The inclusion of this nonlocality in the D state, in addition to the S state, in the potential of Mustafa et al (1992) may be partially the reason for its giving the smaller value of PD = 6·29%, a result that one would expect from the findings of the present work.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The inclusion of this nonlocality in the D state, in addition to the S state, in the potential of Mustafa et al (1992) may be partially the reason for its giving the smaller value of PD = 6·29%, a result that one would expect from the findings of the present work.…”
Section: Discussionsupporting
confidence: 62%
“…of Mustafa et al (1992) has also been found in the w wavefunctions of the present work, as shown in Fig. 4.…”
Section: Deuteron D-state Probabilitysupporting
confidence: 68%
See 1 more Smart Citation
“…Here, the parameter ξ = 0.049 fm −2 was so chosen that (27) would reproduce the experimental root-mean-square radius of deuteron [12]. The dash-dotted curves reproduce the results of cross section calculations made in work [17] in the framework of the virtual pion exchange model.…”
Section: Results Of Calculationsmentioning
confidence: 98%
“…Correlations between the slope b of the neutron form factor G En (q 2 ) at q 2 = 0 and the deuteron root mean square (rms) matter radius r D for different NN-potential models have been used to determine r D [15,16,17].…”
Section: Introductionmentioning
confidence: 99%